IS ISLAM USED AS A POLITICAL IDEOLOGY? WHY AND HOW? PJD MOROCCO AS A CASE STUDY - Driss Bouyahya (European Scientific Journal, ESJ, 2015)
The twentieth century saw a rapid rise of groups of Muslims who use Islam as an ideological weapon for their political ends. This is the current commonly referred to in scholarly and media writings as Islamism and its proponents are designated as 'Islamists', not Muslims, in order to stress that they are attributing an ideological dimension to Islam.Unlike some Islam oriented parties, the PJD (Party of Justice and Development) in Morocco does not focus on the following precepts: madawiyya (a return to the Islamic principles), shumuliyya (a comprehensive application of Islam in all sphere of life) and al da'awa al nidaliyya (a call for struggle to bring about the Islamization of the state and society). To demystify this exception, my approach draws on aspects of Adonis's study of the Islamic tradition (the Constant and the Changing), The Order of Discourse of M. Foucault 1971 and Lotman's idea on the study of text in relation to the outside world or context.